2017
DOI: 10.1523/jneurosci.1181-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Stress Shape the Reward Response Patterns of Serotonin Neurons

Abstract: The ability to predict reward promotes animal survival. Both dopamine neurons in the ventral tegmental area and serotonin neurons in the dorsal raphe nucleus (DRN) participate in reward processing. Although the learning effects on dopamine neurons have been extensively characterized, it remains largely unknown how the response of serotonin neurons evolves during learning. Moreover, although stress is known to strongly influence reward-related behavior, we know very little about how stress modulates neuronal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 57 publications
(38 reference statements)
7
80
0
Order By: Relevance
“…The common behavioral phenotype observed in both male and female mice lacking AdipoR1 in 5-HT neurons is anhedonia. Previous studies have suggested that 5-HT neurons in the DRN encode reward signals [50,51,84,85]. Rewards activate 5-HT neurons [51], and stimulation of 5-HT neurons induces self-administration [50] and resembles the natural reward of sucrose [84].…”
Section: Discussionmentioning
confidence: 99%
“…The common behavioral phenotype observed in both male and female mice lacking AdipoR1 in 5-HT neurons is anhedonia. Previous studies have suggested that 5-HT neurons in the DRN encode reward signals [50,51,84,85]. Rewards activate 5-HT neurons [51], and stimulation of 5-HT neurons induces self-administration [50] and resembles the natural reward of sucrose [84].…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses provide a foundation for further functional dissection of the circuitry of the PVN CRH system. In summary, by combining physiological and behavioral techniques, we provide evidence that reward inhibits PVN CRH neurons to relieve stress, which might aid the development of new clinical strategies for neuropsychiatric disorders, such as depression and anxiety [48,49].…”
Section: Whole-brain Mapping Of Afferents Revealed That Pvn Crh Neuromentioning
confidence: 97%
“…We implanted intraoral cheek fistulae to deliver sucrose or other solution in order to precisely control the duration of volume of each delivery (5 s delivery at 10 mL s -1 ). The surgery followed a previously described procedure [49]. This type of surgery is a delicate cheek implantation technique that is less invasive and has very little pain.…”
Section: Delivery Of Reward Through Intraoral Infusionmentioning
confidence: 99%
“…9,10 Motivational and memory components of reward are crucially mediated by DA transmission in limbic regions including the nucleus accumbens (NAcc) and hippocampus. 21,22 In contrast, 5HT influx to the hypothalamus and cortical regions modulates mood, stress, and emotional valence, 11,23,24 and 5HT transmission to striatal regions moderates DA-driven actions on reward function. 25 Early evidence from experimental animals suggested that DA is critically involved in reward processing.…”
Section: The Pursuit Of Pleasurementioning
confidence: 99%
“…For example, 5HT and DA neurotransmission interact to influence striatal reward responses and their conditioned cues depending on the predicted reward value. 24,39 Downstream signal transduction substrates associated with 5HT receptor activation have also been linked to the actions of these neurochemicals on reward processing, particularly in MDD. 40 For example, successful treatment responses in patients undergoing pharmacotherapy for MDD are marked by increased expression of hippocampal brain-derived neurotrophic factor (BDNF).…”
Section: The Pursuit Of Pleasurementioning
confidence: 99%